2010
DOI: 10.21273/jashs.135.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of a C-repeat Binding Factor Transcriptional Activator from Blueberry Associated with Cold Acclimation and Freezing Tolerance

Abstract: Highbush blueberry (Vaccinium corymbosum) is susceptible to winter freezing injury and frost damage in the spring. As part of an ongoing project to understand the process of cold acclimation, we isolated a C-repeat binding factor (CBF) transcriptional activator gene-coding region from the highbush blueberry cultivar Bluecrop. Expression of the highbush blueberry CBF gene was compared in floral buds of the cold-tolerant nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Overexpression of Arabidopsis CBF genes in other species such as poplar (Benedict et al 2006) and potato (Pino et al 2008), as well as the ectopic expression of CBF genes from other species in Arabidopsis (Welling and Palva 2008;Polashock et al 2010;Kitashiba et al 2004) has resulted in increased levels of freezing tolerance. In these studies, freezing tolerance was generally improved by 2-3°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of Arabidopsis CBF genes in other species such as poplar (Benedict et al 2006) and potato (Pino et al 2008), as well as the ectopic expression of CBF genes from other species in Arabidopsis (Welling and Palva 2008;Polashock et al 2010;Kitashiba et al 2004) has resulted in increased levels of freezing tolerance. In these studies, freezing tolerance was generally improved by 2-3°C.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CBF in cold response and acclimation has been well documented in both herbaceous (Thomashow et al 2001) and woody plants (Welling and Palva 2006). In relation to woody plants, CBF transcription factors have been isolated and shown to be cold-responsive in birch (Betula pendula) (Welling and Palva 2008), poplar (Benedict et al 2006), eucalyptus (Navarro et al 2009;El Kayal et al 2006), grape (Xiao et al 2006), sweet cherry (Prunus avium) (Kitashiba et al 2004), citrus (Champ et al 2007), blueberry (Vaccinium corymbosum) (Polashock et al 2010), and dwarf apple (Malus baccata) (Yang et al 2010) .…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid change is also found in CBF4 from A. thaliana, HbCBF1 from H. brasiliensis, CBFs from Vaccinium myrtillus. It has been previously demonstrated that the change in V. myrtillus CBFs do not inhibit the binding of CBF to the DRE/CRT DNA motif (Polashock et al 2010;Walworth et al 2012;Oakenfull et al 2013). Therefore, the change in cassava MeCBF1 may not inhibit its function.…”
Section: Resultsmentioning
confidence: 98%
“…In this study, we showed a blueberry-derived CBF ( BB-CBF ), which was initially considered to be an orthologue of CBF2 that promoted freezing tolerance in A. thaliana [50], was more similar to A. thaliana DDF1 . Overexpression of the BB-CBF (herein renamed as VcDDF1 ) enhanced cold tolerance in leaves and dormant buds but not in flower tissues of a southern highbush blueberry cultivar [51].…”
Section: Introductionmentioning
confidence: 99%